STRATEGI PENGEMBANGAN PENANAMAN KAKAO DI DESA BONTULA, KECAMATAN ASPARAGA, KABUPATEN GORONTALO - Safitri, Ikraeni; Supriatna, Supriatna; Antameng, Budi Purwanto; Paputungan, Nursiti Aisyah; Suleman, Marwan (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2026)
Cocoa (Theobroma cacao L.) belongs to the Sterculiaceae family and is a plantation crop originating from South America that is now widely grown in tropical regions. Cocoa is used in parts of the fruit such as the skin, pulp, and seeds. Cocoa is a strategic export commodity for Indonesia that generates foreign exchange, but it cannot be denied that the industry is still hampered, resulting in the import of cocoa in finished products. The cocoa development activities conducted in Bontula Village involve local farmers engaged in monoculture farming. The cocoa cultivation in Bontula Village is the result of vegetative propagation using grafting techniques. The activity began with education on the types of cocoa, followed by planting in the community's plantation, which is a demonstration plot. Cocoa development in Bontula Village involves farmers who previously practiced monoculture. Development is carried out through vegetative propagation using grafting techniques. The activity began with education on cocoa types and cultivation techniques, followed by planting on community farmland as a demonstration plot. The results of the activity showed an increase in community awareness of cocoa planting and maintenance, with a plant survival rate of 100%. Keywords :cocoa (theobroma cacao l.), forest farmer group, planting